Sustainable use of natural and chemical coagulants for contaminants removal from palm oil mill effluent: A comparative analysis - Jagaba A.H.; Kutty S.R.M.; Hayder G.; Latiff A.A.A.; Aziz N.A.A.; Umaru I.; Ghaleb A.A.S.; Abubakar S.; Lawal I.M.; Nasara M.A. (Ain Shams University, 2023)
Aluminum compounds; Ammonia; Chemical analysis; Chitosan; Chlorination; Chlorine compounds; Efficiency; Iron compounds; Mixing; Palm oil; Sulfur compounds; Zeolites; Alum; Comparative analysis; Constant parameters; Ferric chloride; Moringa oleifera; Palm oil mill effluents; Removal efficiencies; Statistical packages; Coagulation